Study on Antibacterial Properties of Cellulose Acetate Seawater Desalination Reverse-Osmosis Membrane with Graphene Oxide - Xu, Peilong; Na, Na (Journal of coastal research, 2020)
Xu, P. and Na, N., 2020. Study on antibacterial properties of cellulose acetate seawater desalination reverse-osmosis membrane with graphene oxide. In: Hu, C. and Cai, M. (eds.), Geoinformatics and Oceanography. Journal of Coastal Research, Special Issue No. 105, pp. 246–251. Coconut Creek (Florida), ISSN 0749-0208. In this study, an antibacterial mixed-matrix reverse-osmosis membrane was prepared by adding graphene oxide (GO) through interfacial polymerization on the surface of a cellulose acetate (CA) reverse-osmosis (RO) membrane. The properties and structure of a GO-CA-RO membrane were analyzed by infrared spectrometry and Raman spectrometry, and the antibacterial properties of the GO-CA-RO membrane were tested. The relative inhibition rates of modified membrane products on Escherichia coli and Staphylococcus aureus were 75.93% and 79.98%, respectively. The results showed that a GO-CA-RO membrane prepared by interfacial polymerization has a good antibacterial effect.